Phospholipase Cδ(1) is required for skin stem cell lineage commitment - Nakamura, Yoshikazu (Oxford University Press, 2003)
Phosphoinositide-specific phospholipase C (PLC) is a key enzyme in phosphoinositide turnover and is involved in a variety of physiological functions. Here we report that PLCδ(1)-deficient mice undergo progressive hair loss in the first postnatal hair cycle. Epidermal hyperplasia was observed, and many hairs in the skin of PLCδ(1)-deficient mice failed to penetrate the epidermis and became zigzagged owing to occlusion of the hair canal. Two major downstream signals of PLC, calcium elevation and protein kinase C activation, were impaired in the keratinocytes and skin of PLCδ(1)-deficient mice. In addition, many cysts that had remarkable similarities to interfollicular epidermis, as well as hyperplasia of sebaceous glands, were observed. Furthermore, PLCδ(1)-deficient mice developed spontaneous skin tumors that had characteristics of both interfollicular epidermis and sebaceous glands. From these results, we conclude that PLCδ(1) is required for skin stem cell lineage commitment.